2019
DOI: 10.1029/2018jd030087
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Tropical and Midlatitude Mesoscale Convective Systems as Revealed by Radar Wind Profilers

Abstract: This study contrasts characteristics of mature squall‐line mesoscale convective systems (MCSs) observed by extended ground‐based radar wind profiler (RWP) deployments from the U.S. Department of Energy Atmospheric Radiation Measurement program. This analysis compares the dynamical structure, precipitation, and cold pool properties associated with MCS events over RWP sites in Oklahoma, USA, (midlatitude) to those observed during a 2‐year RWP deployment to Manaus, Brazil, during GoAmazon2014/5 campaign (tropical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(81 citation statements)
references
References 109 publications
9
71
1
Order By: Relevance
“…In Figure 4, we introduce the MAO and SGP data sets by plotting the cumulative mean, 5th (downdraft) and 95th (updraft) percentile profiles for the vertical air motion (| W |> 1.5 m/s) in convective regions. These composites are similar to the ones found in Wang et al (2019) and other observational summaries. In Figure 4b, we demonstrate that when segregating according to updraft‐only ( W > 1.5 m/s) and downdraft‐only ( W < ‐1.5 m/s) conditions, SGP events are associated with more intense air motions.…”
Section: Core Results Within Mature Mcs Convective Linessupporting
confidence: 91%
See 3 more Smart Citations
“…In Figure 4, we introduce the MAO and SGP data sets by plotting the cumulative mean, 5th (downdraft) and 95th (updraft) percentile profiles for the vertical air motion (| W |> 1.5 m/s) in convective regions. These composites are similar to the ones found in Wang et al (2019) and other observational summaries. In Figure 4b, we demonstrate that when segregating according to updraft‐only ( W > 1.5 m/s) and downdraft‐only ( W < ‐1.5 m/s) conditions, SGP events are associated with more intense air motions.…”
Section: Core Results Within Mature Mcs Convective Linessupporting
confidence: 91%
“…Those statements were based on differences between normalized histograms of the vertical velocity retrievals under various regime breakdowns that sampled a wide variety of isolated to organized convective events. For these particular Amazon MCS events, Wang et al (2019) suggested that Amazon dry or transitional seasons favored more intense maximum updraft profile signatures (distribution tails), with the dry season favoring deeper and more intense downdrafts. However, Wang et al (2019) were careful to indicate those results as noisy and/or limited by event sampling.…”
Section: Core Results Within Mature Mcs Convective Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of tropical DMC-PBL interaction have demonstrated the importance of characterizing morphological aspects of the convective activity that disturbs the PBL with the aid of radar imagery (e.g., SR98; Schiro and Neelin, 2018;Wang et al, 2019). In this study, all four of the storm events investigated consisted of either a single cell or a small cluster of multicell storms (Moller et al, 1994).…”
Section: Overview Of the Dmc Eventsmentioning
confidence: 90%